Toward a framework for identifying attitudes and intentions to music acquisition from legal and illegal channels - Dilmperi, Athina; King, Tamira; Dennis, Charles (Wiley, 2017)
Technological developments have had a profound effect on modern music acquisition, allowing people to share music over the Internet for free. The research identifies the antecedents of consumers’ attitudes and intentions to acquire music from various channels. The paper reports findings of a structured questionnaire survey of university students in the United Kingdom and Greece (n = 511). Using structural equation modeling, the authors conclude that consumers’ intention to acquire music via a legal channel is influenced by idolatry (IDL), the perceived quality of music (PQM), the perceived likelihood of punishment (PLP; digital legal channel only), and their subjective norm. On the other hand, intention to acquire music via an illegal channel is influenced by the perceived benefits of piracy. The price of legitimate music was only significant for the illegal street vendor channel, whereas IDL had a positive effect on illegal downloading. Gender had moderating effects on PLP and attitude, and income-moderated attitude and intention from P2P platforms. The findings carry important implications for academic researchers, practitioners, and policymakers.